A new approach to measuring materialism - Trinh, Viet; Phau, Ian (Korean Scholars of Marketing Science, 2012)
This paper presents a different set of measurement for materialism based on the theoretical foundation of Richins and Dawson. After various tests, a new 16-item scale was developed to measure four components of materialism, namely material success, material happiness, material essentiality and material distinctiveness.